Effect of Radiotherapy Combined With Pembrolizumab on Local Tumor Control in Mucosal Melanoma Patients - Kim, Hyun Ju; Chang, Jee Suk; Roh, Mi Ryung; Oh, Byung Ho; Chung, Kee-Yang; Shin, Sang Joon; Koom, Woong Sub (Frontiers in Oncology, 2019)
Objective: Mucosal melanoma is an aggressive malignancy with a poor response to conventional therapies. The efficacy of radiotherapy (RT), especially combined with immune checkpoint inhibitors (ICIs), for this rare melanoma subtype remains unknown. We investigated the reciprocal effect of RT and ICI on mucosal melanoma patients. Materials/Methods: We identified 23 patients with 31 tumors who were treated with RT between July 2008 and February 2017. All patients received RT for primary or metastatic gross tumor mass with a median dose of 4 Gy per fraction (range 1.8–12 Gy). Eleven patients (14 lesions) were treated with RT alone, whereas 12 (17 lesions) were administered pembrolizumab combined with RT (ICI+RT group). The local control (LC) and adverse event (AE) rates were compared between the groups. Eight patients with metastatic mucosal melanoma treated with ICI alone during the same study period were included as a comparison group. Results: The median follow-up period was 17.4 (range 3.7–95.2) months. The target lesion control rate at 1-year was significantly higher in the ICI+RT group than in the RT-alone group or ICI-alone group (94.1% vs. 57.1% vs. 25%; P<.05). No abscopal effect was observed in our cohort. Treatment-related AEs were not significantly increased in the combined treatment group compared with the RT-alone group (P>.05). No grade ≥3 AEs occurred in the ICI+RT group. Conclusions: Besides RT acting as an immune adjuvant, ICI might have a radiosensitizing effect and may increase LC without severe toxicity. We have initiated a phase II study to determine the effects of RT in patients with melanoma undergoing anti-PD1 (NCT04017897).